2020
DOI: 10.1016/j.jde.2020.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability of elliptic relative equilibria of restricted four-body problem

Abstract: In this paper, we consider the linear stability of the elliptic relative equilibria of the restricted 4-body problems where the three primaries form a Lagrangian triangle. By reduction, the linearized Poincaré map is decomposed to the essential part, the Keplerian part and the elliptic Lagrangian part where the last two parts have been studied in literature. The linear stability of the essential part depends on the masses parameters α, β with α ≥ β > 0 and the eccentricity e ∈ [0, 1). Via ω-Maslov index theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…For the Euler collinear case, we still have two cases: the 4 bodies are collinear and the four bodies span R 2 . The case of the four bodies form a collinear configuration has been discussed in [13]. In this paper, we focus on the case of 4 bodies span R 2 .…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Euler collinear case, we still have two cases: the 4 bodies are collinear and the four bodies span R 2 . The case of the four bodies form a collinear configuration has been discussed in [13]. In this paper, we focus on the case of 4 bodies span R 2 .…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…One well-studied case is the elliptic rhombus solution [10,12,16] which are linearly instable. For the restricted 4-body problem with three primaries forming Lagrangian equilateral configuration, the full bifurcation diagram of the stability and instability has been obtained for all possible masses and all eccentricity [9,13]. Furthermore, one stable region of the linear stability has been found.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Because of the symmetry of the problem, the equations for m 2 and m 4 are identical to equations ( 7) and (8). e equation for m 0 is identically zero.…”
Section: Rhomboidal Central Configurationsmentioning
confidence: 99%
“…Llibre and Mello [7] classified the central configurations of the four-body problem. Liu and Zhou [8] investigated the four-body problem with three masses forming a Lagrangian triangle, used the bifurcation diagram of linearly stable and unstable regions, and found two linearly stable subregions with respect to α, β, and e. Deng et al [9] investigated the CC of the four-body problem with equal masses and showed that, for the planar Newtonian four-body problem having adjacent equal masses i.e., m 1 � m 2 ≠ m 3 � m 4 and equal lengths for the two diagonals, any convex noncollinear CC must have a symmetry and must be an isosceles trapezoid. ey also showed that when the length between m 1 and m 4 equals the length between m 2 and m 3 , the CC is also an isosceles trapezoid.…”
Section: Introductionmentioning
confidence: 99%
“…In [20] the restricted four-body problem was studied in the symmetric case (it agrees with other results) and in the case where A lies outside the Lagrange triangle (6 configurations). In [22] the authors use functional analytic methods and a version of Maslov index to study stability of some situations from [20].…”
Section: Introductionmentioning
confidence: 99%